The Role of Principal Leadership in Improving the Quality of Education at SMP Negeri 2 Kualuh Selatan, North Labuhan Batu Regency - Adinda Julia Putri; Makmur Syukri (Manajia: Journal of Education and Management, 2024)
The current principal’s leadership cannot be said to be good because this can be seen from the performance that has not been optimal. Principal leadership plays an important role, but some principals are not able to carry out their duties properly. This of course will greatly affect school activities that have an impact on the quality of education. This study aims to analyze the principal’s leadership in improving the quality of education. This type of research uses literature review which uses 6 articles. The data analysis technique used qualitative analysis. The results showed that the leadership of the principal who had changes was able to improve the quality of education. Change by seeking innovation programs. Improve student management in school culture and discipline it. The principal’s leadership is formed by his nature that gives a sense of comfort to all school members. A good principal is able to cultivate a school culture and discipline, become a work partner, create cooperation among all school members to form a friendly and purposeful school environment. Thus, the leadership of the principal improves the quality of education.